2001
DOI: 10.1074/jbc.m103305200
|View full text |Cite
|
Sign up to set email alerts
|

The Catalog of Human Hair Keratins

Abstract: The human type II hair keratin subfamily consists of six individual members and can be divided into two groups. The group A members hHb1, hHb3, and hHb6 are structurally related, whereas group C members hHb2, hHb4, and hHb5 are rather distinct. Specific antisera against the individual hair keratins were used to establish the two-dimensional catalog of human type II hair keratins. In this catalog, hHb5 showed up as a series of isoelectric variants, well separated from a lower, more acidic, and complex protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 271 publications
(101 citation statements)
references
References 41 publications
5
95
0
1
Order By: Relevance
“…In beard hairs, cells in the lowermost portion of the central medulla also contained HOXC13 protein in their nuclei. Accordingly, we generated ␤-galactosidase reporter gene constructs with promoter fragments of type I hair keratin genes hHa2, hHa5, and hHaA, which are expressed in these regions (13,15,16), for cotransfection studies with a HOXC13 expression vector. These studies clearly showed that hair keratin promoters strongly activated the reporter gene in the presence of functional but not homeobox deleted HOXC13.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In beard hairs, cells in the lowermost portion of the central medulla also contained HOXC13 protein in their nuclei. Accordingly, we generated ␤-galactosidase reporter gene constructs with promoter fragments of type I hair keratin genes hHa2, hHa5, and hHaA, which are expressed in these regions (13,15,16), for cotransfection studies with a HOXC13 expression vector. These studies clearly showed that hair keratin promoters strongly activated the reporter gene in the presence of functional but not homeobox deleted HOXC13.…”
Section: Discussionmentioning
confidence: 99%
“…IIF on cryostat sections of plucked beard hair follicles and human scalp sections was carried out as described previously (13,15). The HOXC13 antiserum was generated using the synthetic oligopeptide PEPSGALPDGDDLS-C as antigen.…”
Section: Hair Keratin Reporter Plasmids and Deletion Constructs-promotermentioning
confidence: 99%
See 2 more Smart Citations
“…Hair keratins, a subset of the large keratin family whose members are found in all cells of epithelial origin (3,4), represent two multigene families, the type I (acidic) and type II (basic) families that comprise 15 members in humans (5,6). They form the 8 -10-nm intermediate filaments of trichocytes by co-polymerization of type I and type II members, which are differentially expressed during hair fiber development (7,8). KAPs, which form the matrix between the hair keratin intermediate filament bundles through extensive disulfide bond cross-linking with cysteine residues in the head and tail domains of hair keratins, possess either high cysteine or high glycine-tyrosine content (2) and are further divided into three broad groups containing, to date 17 families.…”
mentioning
confidence: 99%